Advanced SAP Crystal Reports 2011 training - Vaccaro, Guy (InfiniteSkills, 2012)
"In this Advanced Crystal Reports 2011 training course, expert trainer and author Guy Vaccaro covers advanced topics and tools available to you in Crystal Reports. This course is for users that are already familiar with the basic operation of Crystal Reports, and want to get more in-depth with its capabilities. Guy starts you off easy, with a quick review of some of the basics of Crystal Reports, and then take you right into some of the more complex features. You begin with conditional formatting then move on to working with parameter fields and report alerts. You will learn how to create multiple sections, and sub reports. Advanced charting is covered, along with cross-tabs, formulas, even a chapter on SQL commands. You finish the training course with a quick look at the data map tool and how to distribute your reports. By the completion of this computer based training video on SAP Crystal Reports 2011, you will have a deeper grasp of the advanced features that are available to you, allowing you to present your data in easy to understand and visually appealing ways. Working files are included to allow you to work with the author throughout this training course."--Resource description page.